2014
DOI: 10.5935/0104-7795.20140002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of musculoskeletal pain among nursing surgery teams

Abstract: Among the health professions, nursing, in particular, has been affected by musculoskeletal disorders. The WMSD produce changes in the lives of these workers, impossible of them held daily activities and labour. Objective: Investigating the prevalence of musculoskeletal pain and associated with the quality of life in nursing professionals who work in surgery teams. Method: Cross-sectional study conducted between March 2011 and January 2012 in a tertiary university hospital in southern Brazil. We evaluated 110 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
1
7
0
4
Order By: Relevance
“…Another factor possibly associated with the development of discomfort is the lack of physical training due to the sedentary lifestyle. These findings were highlighted in a previous study (1) in which was reported a high rate of workers not practicing any type of physical activity in their daily lives.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Another factor possibly associated with the development of discomfort is the lack of physical training due to the sedentary lifestyle. These findings were highlighted in a previous study (1) in which was reported a high rate of workers not practicing any type of physical activity in their daily lives.…”
Section: Discussionmentioning
confidence: 58%
“…Infectious-contagious diseases and work-related musculoskeletal disorders (WMSD) are among the most frequent occupational diseases in nursing professionals. There is also physical, psychic and organizational burden that may be associated with standing work, weight lifting, inadequate postures and psychophysical aspects (1) . WMSDs can cause dysfunction and disability and impose high costs with payed sick leave.…”
Section: Introductionmentioning
confidence: 99%
“…The work-related musculoskeletal disorders (Dort), diseases also evidenced in this study, are associated with exposure to physiological burden, especially by adopting inadequate postures and excessive manipulation of weight that cause changes in physical, psychological and psychosocial order. The chronic disease causes signs and symptoms as stress, depression, anxiety, insecurity, fear, adopting introverted attitudes and mood alterations, also committing to social and family life (17) . Physical symptoms lead to frequent worker absences.…”
Section: Discussionmentioning
confidence: 99%
“…As reason for sick leave due to musculoskeletal pain, the main complaint was low back pain (34%). The group that did not report musculoskeletal pain showed better quality of life index in functional capacity, physical aspects, pain, vitality, social functioning and mental health (18) . As for the effectiveness of auricular acupuncture for the control of pain, a systematic review and meta-analysis included 17 clinical trials in English, eight for perioperative, four for acute pain and five for chronic pain, which used sham auriculotherapy, placebo, control or medication use for pain.…”
Section: Discussionmentioning
confidence: 91%